Advanced recycled carbon fiber (rCF) reinforced PEEK composites – excellent alternatives for high-performance tribomaterials. (December 2022) - Lin, Leyu; Zhao, Yuxiao; Xu, Yao; Sun, Chong; Schlarb, Alois K.
Abstract: Serious environmental pollution, increasing energy consumption, and greenhouse gas emissions as well as raw material resources scarcity are huge challenges in our today's society. In order to realize sustainable development and preserve the environmental balance, the 3R rule is applied, which corresponds to reduce, reuse and recycle. In materials development, this rule needs to be also considered for the sustainable development. In the present study, we used different recycled carbon fibers to manufacture polyetheretherketone-based tribocomposites. The results demonstrate that recycled carbon fibers, independent of their recycling histories, can serve as excellent candidates for preparing high-performance tribocomposites. The friction and wear performance are much better than those of a commercially available product, which is quite close to the best tribological performance of distinct high-performance tribomaterials reported in the literature.